Role of fine needle aspiration cytology (FNAC) in the diagnosis of soft tissue tumors - Gulzar, Jasmeen; Yasin, Syed Besina; Khan, Subuh Parvez; Bashir, Naheena (International Journal of Research in Medical Sciences, 2017)
Background: Soft tissue tumors constitute a large and heterogenous group of neoplasms. Benign tumors out number their malignant counterparts by a ratio of about 100:1 in hospital population. FNAC has emerged as a major outpatient procedure for the diagnosis of soft tissue tumors due to low cost of the procedure, less complications, feasibility, quick results and high therapeutic efficiency with specificity and sensitivity of approximately 95%. The diagnostic accuracy of FNAC of soft tissue tumors in distinguishing benign and malignant lesion is also very high. The objectives of this study were to study the role of FNAC in the diagnosis of soft tissue tumors and its correlation with histopathology. Also, this study aimed at studying various cytomorphological patterns of soft tissue tumors and correlating cytological grading with histopathological grading. Methods: It was a hospital based study of 5 years which included 479 patients of all age groups, clinically presenting with soft tissue swellings. FNAC was performed. Smears were stained with Papanicolaou (PAP)/May Grunwald Geimsa (MGG). The cytological details of soft tissue tumors were studied and broadly classified into benign, malignant and indeterminate and suspicious. Cytomorphological subtyping and grading of tumors on FNAC was done. The cytological findings were correlated with the histopathological results, wherever available. Results: Benign tumors comprised of 423 cases (88.3%) and malignant tumors comprised 56 cases (11.69%)only. Maximum number of cases were seen in well differentiated/lipomatous group (339 cases) followed by spindle cell category (88 cases). Histopathological correlation carried out in 136 out of 479 cases (benign:111 and malignant :25) revealed that out of 111 cases diagnosed as benign by cytology, one case was malignant (liposarcoma) and among 25 malignant cases diagnosed by cytology one case was benign (myofibroblastoma). Overall sensitivity and specificity of FNAC was 96% and 99% respectively. Comparison of cytological and histopathological grading of 24 sarcomas showed overall concordance of 75%. Conclusions: FNAC is an excellent diagnostic modality in early diagnosis of soft tissue tumors. FNAC is highly reliable and obviates surgical procedures especially in high risk patients thus facilitating initiation of appropriate therapy and saving time and manpower. It is also highly sensitive in detecting benign soft tissue tumors and highly specific for malignant soft issue tumors.